ASSESSING SPEAKING SKILLS (Ustozlar uchun, 2025)
This article examines the principles, methods, and challenges associated with assessing speaking skills in English as a foreign language (EFL) contexts. Speaking assessment plays a vital role in evaluating learners’ communicative competence. The paper emphasizes the importance of reliability, validity, and practicality in designing speaking tests and provides an overview of assessment formats commonly used in educational settings.